A multicenter, randomized study to select the minimum effective dose of estetrol (E4) in postmenopausal women (E4Relief): part 1. Vasomotor symptoms and overall safety - Gaspard, Ulysse (Menopause, 2020)
OBJECTIVE: The aim of this study was to select the minimum effective dose of estetrol (E4) for the treatment of vasomotor symptoms in postmenopausal women. METHODS: This was a multicenter, randomized, double-blind, placebo-controlled study. Postmenopausal women (n = 257, of whom 32 were hysterectomized) aged 40 to 65 years, with ≥7 moderate to severe hot flushes (HFs) per day, or 50 or more moderate to severe HFs weekly, received 2.5, 5, 10, or 15 mg E4, or placebo once-daily for a period of 12 weeks. Efficacy was assessed by recording the frequency and severity of HFs. Overall safety was assessed by recording adverse events, measuring endometrial thickness, and monitoring bleeding patterns. Treatment groups were compared using analysis of covariance. RESULTS: The frequency of moderate to severe HFs decreased with all E4 doses. The difference in the percentage change of weekly HF frequency was significant for 15 mg E4 versus placebo at both W4 (−66% vs −49%, P = 0.032) and W12 (−82% vs −65%, P = 0.022). The decrease in severity of HFs was significantly more pronounced for 15 mg E4 than for placebo at both W4 (−0.59 vs −0.33, P = 0.049) and W12 (−1.04 vs −0.66, P = 0.049); the other doses failed to achieve statistical significance. In nonhysterectomized women, endometrial thickness increased during treatment and normalized following progestin treatment at study completion. No endometrial hyperplasia was observed. CONCLUSIONS: Estetrol 15 mg is considered to be the minimum effective daily oral dose for treatment of vasomotor symptoms. Its current seemingly favorable safety profile is further to be confirmed in phase 3 clinical development. Video Summary:.